An evaluation of the competency-based health skills training on the performance of community volunteer health workers in selected Barangays of San Juan Batangas - Acop, Jacqueline G.; Acop, Jacqueline G.; Alvaro, Kristine I.; Amoroso, Michelle C.; Barua, Ranee Ruth R.; Ceblano, Christine A.; Coloma, Keigthley Faye P.; Cruz, Jessica Mae C.; Cua, Emmeline Elaine L.; Espinosa, Paulynne G.; Geron, Paula Blanca M.; Igsoc, Katrina P.; et al. (Manila College of Nursing University of the Philippines Manila, 2008)
This study describes the effect of the Competency-Based Training on the Community Volunteer Health Workers’ (CVHWs) performance on vital signs, height and weight taking. The training program aims to enhance the CVHWs’ competencies in assessing clients who seek health care from them.

The evaluative study was conducted after 11 weeks that consisted the training needs assessment and practicum involving 74 CVHWs assigned to Barangays Ticalan, Puting Buhangin, Abung, Calubcub-2, Subukin, Bataan, and Hugom of San Juan, Batangas. Data were collected through pretest and three (3) post-test sessions with two weeks interval. At post-test 3, only 58 CVHWs were able to attend. Standard Test Questionnaires and Performance Evaluation Checklist developed by the investigators were used as basis for evaluation.

Results were analyzed using descriptive statistics, T-test of difference for paired samples, and item analysis. There have been observed significant increase in the performances of the subjects in terms of competency and efficiency between pre-test and post-test 1, and between post-test 2 and post-test 3. Between post-test 1 and post-test 2, a significant decrease in the performance was observed (t=3.95857, p-value= 0.000). Overall, there is a significant increase in the performance of the subjects prior to and post-training.

The characteristics of the CVHWs are taken into account in terms of age, educational attainment, years of service as CVHW, and previous training on vital signs, height, and weight taking. The subjects who developed the competency had the following characteristics: age
range of 25-69 years old, educational attainment range of elementary undergraduate to college graduate, and years of service range of less than a year to 25 years. 63.63% had exposure to previous non-competency based trainings while 36.37% had none.

The results of the study point to the conclusion that the Competency-Based Training on Vital Signs, Height and Weight Taking has a positive effect on the performance of its participants.
Accomplishment report (In partial fulfillment of the requirements for N121.2: Intensive Community Experience Community-Based) -- University of the Philippines Mania, April 2008.
Keywords: Intensive community experience